The Molly Maguires - Martin Ritt; Zerbe, Anthony, 1936-; Art Lund; Bethel Leslie; Frank Finlay; Richard Harris; Samantha Eggar; Sean Connery (USA Paramount Pictures, 1970)
Life is rough in the coal mines of 1876 Pennsylvania. A secret group of Irish emigrant miners, known as the Molly Maguires, fights against the cruelty of the mining company with sabotage and murder. A detective, also an Irish emigrant, is hired to infiltrate the group and report on its members. But on which side do his sympathies lie?
Life is rough in the coal mines of 1876 Pennsylvania. A secret group of Irish emigrant miners, known as the Molly Maguires...
Walter Bernstein
Language(s): English, German, Spanish, French, Italian Subtitle(s): Arabic, Bulgarian, Czech, Danish, German, Greek, English, French, Spanish, Hebrew, Serbo-Croatian, Icelandic, Italian, Hungarian, Dutch, Norwegian, Polish, Portoguese, Romanian, Slovenisn, Finnish, Swedish, Turkish
Keywords: History; Drama